Degradation of Customary Inheritance Law in the Sai Batin Lampung Tribe - Sopyan, Yayan; Nusirwan, Nusirwan; Rais, Isnawati; Aswawi, Asmawi (Universitas Islam Negeri Raden Intan Lampung, 2020)
The Sai Batin indigenous people use the “jujur” form of marriage the male majorate inheritance system, a system in which the oldest son is entitled to all inheritance and is the successor of their descendants. So strong is the position of sons in the family that if a family does not have a son, then the family is considered as having no or broken offspring. For this reason, in the Sai Batin kinship system, the adoption of a son, either from an internal or external family, is an alternative solution. This research is qualitative research using the Islamic Law Anthropology approach. In the data collection stage, the writer used the dept-interview technique combined with a survey. This research concludes that although most of the Sai Batin tribes still adhere to the customary inheritance system, however, there has been a tendency to no longer use customary law, especially in matters of inheritance, because it is considered unfair. This is indicated by the tendency of parents to bequeath property to all their children through a grant mechanism or to distribute inheritance based on Islamic inheritance law. This change is influenced by many factors, including the most dominant factors are education, economy, and social interaction.